1996
DOI: 10.1136/bmj.313.7050.143
|View full text |Cite
|
Sign up to set email alerts
|

Chronic memory impairment after cardiac arrest outside hospital

Abstract: Clinically important impairment of memory was common after cardiac arrest outside hospital. Improvement in response times of emergency services could reduce the severity of such deficits. With an increasing numbers of people expected to survive cardiac arrest outside hospital, rehabilitation of those with memory deficit merits specific attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 26 publications
5
88
1
7
Order By: Relevance
“…A recent study examining cognitive performance and specifically executive function in a population of general intensive care survivors found these functions to be very significantly impaired at least three months after discharge from ICU. 24 Grubb et al reported a correlation between resuscitation delays and memory impairment, 4 but the prospective study of Roine et al 2 did not find a similar correlation, and the prospective study of van Alem et al 3 reported only a weak correlation. It thus seems that long delays in the resuscitation do not exclude the possibility of good cognitive outcome.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A recent study examining cognitive performance and specifically executive function in a population of general intensive care survivors found these functions to be very significantly impaired at least three months after discharge from ICU. 24 Grubb et al reported a correlation between resuscitation delays and memory impairment, 4 but the prospective study of Roine et al 2 did not find a similar correlation, and the prospective study of van Alem et al 3 reported only a weak correlation. It thus seems that long delays in the resuscitation do not exclude the possibility of good cognitive outcome.…”
Section: Discussionmentioning
confidence: 71%
“…One study with 35 subjects focusing on memory deficits found moderate to severe memory impairment in 37% of survivors at 7 months after CA. 4 Quantitative electroencephalography (Q-EEG) and P300 event-related potential have been studied in various disorders of brain function with cognitive impairment, especially in dementing illnesses and mild cognitive decline. 5 Q-EEG uses computer software to provide topographic analysis of brain activity.…”
mentioning
confidence: 99%
“…Previous studies of cardiac arrest quality of life were relatively small and did not attempt to identify the predictors of very good quality of life. [11][12][13] These other studies used a variety of instruments, including the Sickness Impact Profile, the Medical Outcome Short Form 36, and the Functional Status Index. 27 Our study is the first to use the HUI3 for an exclusively out-of-hospital cardiac arrest population.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Several investigators have recently evaluated the outcomes or quality of life of survivors of out-of-hospital cardiac arrest. [11][12][13][14] We have previously found that most patients who survive to hospital discharge have quite good quality of life and functional status. 15 Little is known, however, about the factors that may correlate with or lead to better functional status for these cardiac arrest survivors.…”
mentioning
confidence: 99%
“…9,10 In a recent review, 30% to 50% of survivors after cardiac arrest were reported to suffer from cognitive impairment. 11 The generalizability of previous studies is poor because of small sample sizes, [12][13][14] missing data, 13,14 and patient selection, that is, the exclusion of those with a poor outcome, 14 inclusion of only patients with severe symptoms, 12 or absence of a nonarrest control group. 11 Optimally, OHCA survivors should be evaluated for the cognitive functions known to be most affected: memory, attention, and executive functions.…”
Section: Clinical Perspective On P 1349mentioning
confidence: 99%